Clinical characteristics and prognostic factors of liver cirrhosis patients with systemic inflammatory response syndrome. Issue 11 (19th May 2017) - Yang, Danhong; Xie, Yuanjun; Pan, Hongying; Huang, Yicheng; Dai, Yining; Tong, Yongxi; Chen, Meijuan
Abstract : Aim: Our objective is to study the clinical characteristics of cirrhosis patients with SIRS and investigate its prognostic factors. Methods: We analyzed 285 consecutive patients and their data were evaluated retrospectively. Data were compared in patients with/without SIRS during hospitalization. Univariate and multivariate Cox regression analyses were undertaken separately for cirrhotic patients with SIRS to assess predictive factors for 90‐day mortality. Results: The mortality was 38.24% (52/136) in patients with SIRS and 6.04% (9/149) in patients without SIRS for 90‐day follow‐up ( P < 0.001). The univariate analysis showed gastrointestinal hemorrhage ( P < 0.001), hepatic encephalopathy ( P < 0.001), albumin <30 g/L ( P < 0.037), creatinine (Cr) >175 µmol/L ( P < 0.001), cholinesterase(ChE) activity <3000 U/L ( P = 0.019), white blood cell count ≥10 000 (109/L) ( P = 0.018), neutrophils ≥80% ( P = 0.018), C‐reactive protein (CRP) ≥25 mg/L ( P < 0.001), procalcitonin ≥1.0 ng/mL ( P = 0.007), Child–Pugh class C ( P < 0.001), septicemia ( P < 0.001), pulmonary infection ( P < 0.001), multi‐site infection ( P = 0.001), acute‐on‐chronic liver failure (ACLF) ( P < 0.001), and advanced hepatocellular carcinoma (HCC) ( P < 0.001). In multivariate analysis, only Cr ≥175 µmol/L (hazard ratio [HR] = 2.768; confidence interval [CI], 1.53–5.04; P = 0.001), C‐reactive protein ≥25 mg/L (HR = 3.179; CI, 1.772–7.03; P = 0.004), multi‐site infection (HR = 19.427; CI, 7.484–50.431; P < 0.001), ACLF (HR = 7.308; CI, 3.048–17.521; P < 0.001), advanced HCC (HR = 2.523; CI, 1.019–6.248; P = 0.045) were independent predictors of 90‐day mortality in cirrhotic patients with SIRS. Conclusion: Cr ≥ 175 µmol/L, CRP ≥ 25 mg/L, multi‐site infection, ACLF, and advanced HCC independently predicted a higher rate of 90‐day mortality in liver cirrhosis with SIRS